Information quality and source credibility influence purchase intention in live-stream advertising: a moderated mediation model - He, Changhua; Hashim, Norliana; Kamarudin, Syafila; Yu, Mengyao; Shi, Lijun; Li, Chengen; Peng, Chen (Scientific Journal Publishers, 2026)
This study integrated the elaboration likelihood model and the theory of reasoned action to explore the effect of information quality and source credibility on purchase intention in the context of live-stream advertising. The sample comprised 400 respondents with live-stream shopping experience. We found that information quality and source credibility significantly and positively affected users’purchase intention, with attitude partially mediating this relationship. Advertising involvement positively moderated the effect of information quality on purchase intention through attitude but negatively moderated the effect of source credibility. We recommend that live-stream advertisers prioritize enhancing information quality and influencer credibility to improve positive user attitude, and tailor marketing strategies based on audience involvement levels by providing detailed product information for highly involved users and fostering interaction and emotional connections for low-involvement viewers. This targeted approach could maximize engagement and drive purchase intention.